PERBANDINGAN MODEL PEMBELAJARAN OSBORN DAN MODEL PEMBELAJARAN MATEMATIKA INTERAKTIF BERBASIS KOMPUTER TERHADAP HASIL BELAJAR SISWA KELAS X TKJ SMK NEGERI 1 SINJAI - Musdalifah; Sudirman P; Nurjannah (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2022)
This study aims to compare student learning outcomes in mathematics with the use of Osborn and computer-based interactive mathematics learning model in class X TKJ SMKN 1 Sinjai. This type of research is an experimental research with a quantitative approach with a pretest postest control group design research design. The population in this study were students of class X TKJ SMK Negeri 1 Sinjai. While the sample used is simple random sampling. Based on the descriptive analysis of student learning outcomes in class X TKJ 1 after the application of the Osborn learning model as a control class, the average pre-test of the Osborn learning model was 76.80 and the post-test was 79.25 which was greater than the KKM (65). Based on the inferential analysis, the results of this study indicate that the Sig. (2-tailed) in the paired sample t-test of 0.000 where the value is less than 0.05. Thus, it can be concluded that there are differences in learning outcomes between Osborn and the computer-based interactive learning model for the tenth graders of TKJ SMK Negeri 1 Sinjai.